TOC INDONESIAN JOURNAL OF LEGAL AND FORENSIC SCIENCES Volume 1 tahun 2015 - Wirasuta, gelgel (Indonesian Journal of Legal and Forensic Sciences (IJLFS); Vol 5 (2015): Indonesian Journal of Legal and Forensic Sciences, 2015)
INDONESIAN JOURNAL OF LEGAL AND FORENSIC SCIENCES Volume 1 tahun 2015